2019
DOI: 10.12688/f1000research.17196.1
|View full text |Cite
|
Sign up to set email alerts
|

mTOR as a central regulator of lifespan and aging

Abstract: The mammalian/mechanistic target of rapamycin (mTOR) is a key component of cellular metabolism that integrates nutrient sensing with cellular processes that fuel cell growth and proliferation. Although the involvement of the mTOR pathway in regulating life span and aging has been studied extensively in the last decade, the underpinning mechanisms remain elusive. In this review, we highlight the emerging insights that link mTOR to various processes related to aging, such as nutrient sensing, maintenance of prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
238
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(272 citation statements)
references
References 275 publications
2
238
0
4
Order By: Relevance
“…Another interesting relation between mTOR pathway and autophagy is the association to lifespan and aging; mainly because it has been observed that inhibition of mTOR could bring as a consequence delay of aging due to autophagy stimulation resulting in a mitophagy increase (172). In fact, it is well-documented that inhibition of key components of mTOR and its counterpart in invertebrates TOR pathways, results in an extension of life span in part by the influence of mTOR on the called "hallmarks of aging, " an interesting an extensive review about this subject is broadly reviewed in Papadopoli publication (173).…”
Section: Glutaminolysis and Mtorc1 In Cancermentioning
confidence: 99%
“…Another interesting relation between mTOR pathway and autophagy is the association to lifespan and aging; mainly because it has been observed that inhibition of mTOR could bring as a consequence delay of aging due to autophagy stimulation resulting in a mitophagy increase (172). In fact, it is well-documented that inhibition of key components of mTOR and its counterpart in invertebrates TOR pathways, results in an extension of life span in part by the influence of mTOR on the called "hallmarks of aging, " an interesting an extensive review about this subject is broadly reviewed in Papadopoli publication (173).…”
Section: Glutaminolysis and Mtorc1 In Cancermentioning
confidence: 99%
“…Rapamycin, (International Nonproprietary Name: sirolimus), is an inhibitor of mTOR, which results in an extended life span and prevents age-related diseases [157][158][159][160] by mediating SIRT1 expression [161,162]. mTOR is a serine-threonine kinase that plays a role in modulating cell survival, growth, proliferation, motility, protein synthesis and transcription [163] and inducing autophagy [164][165][166].…”
Section: Rapamycinmentioning
confidence: 99%
“…Autophagy has a central role in promoting health and longevity by removal of toxic material such as damaged organelles and large protein aggregates while this process is impaired in neurodegenerative diseases and αSyn pathology [80,81]. The p.A53Tproteome shows that neurons are under stress as proteins involved in the UPR or the heat-shock stress response, proteasome assembly and regulation, known to be orchestrated by mTORC1 in neurons, are significantly upregulated [77]. Accumulation of unfolded or misfolded proteins in p.A53T-neurons, including a large portion of RBPs that have an intrinsic propensity to aggregate, would result in misregulation of the autophagic system.…”
Section: Discussionmentioning
confidence: 99%